Penegakan Hukum Terhadap Ketidakpatuhan Pembayaran Pajak Bumi Dan Bangunan di Surakarta - Pricellia Griselda Puspitadevi Gunarso; Wasis Sugandha (Jurnal Discretie, 2020)
This study examines the problem of how law enforcement against community noncompliance in the payment of land and building tax in the rural and urban sectors (PBB-P2) in Surakarta and what are the obstacles in the payment of land and building tax in the rural and urban sectors in Surakarta. Research shows that law enforcement against non-compliance with PBB-P2 payments in Surakarta should be improved, this can be seen from the frequent tax breaks that result in ineffective sanctions for taxpayers who are in arrears. Even though BPPKAD has provided many innovations to encourage people to pay taxes on time, look at people who are in tax arrears. Public awareness of the importance of paying taxes on time is still not good, as seen from an increase in the number of tax arrears from 2017 to 2019.